2016
DOI: 10.18632/oncotarget.10429
|View full text |Cite
|
Sign up to set email alerts
|

A key role for transketolase-like 1 in tumor metabolic reprogramming

Abstract: Metabolic reprogramming, a crucial cancer hallmark, shifts metabolic pathways such as glycolysis, tricarboxylic acid cycle or lipogenesis, to enable the growth characteristics of cancer cells. Here, we provide evidence that transketolase-like 1 (TKTL1) orchestrates aerobic glycolysis, fatty acid and nucleic acid synthesis, glutamine metabolism, protection against oxidative stress and cell proliferation. Furthermore, silencing of TKTL1 reduced the levels of sphingolipids such as lactosylceramide (a sphingolipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 54 publications
3
44
0
Order By: Relevance
“…Dietary studies have also indicated that the inhibition of the PPP minimizes tumor growth [13,36,37]. Although it has been reported that TKTL1 contributes to total transketolase activity [38], with a similar metabolic role to TKT, this protein also seems to participate in other metabolic processes such as DNA hypomethylation, fatty acid synthesis, and even the one-substrate reaction catalyzing the transformation of xylulose-5-phosphate into glyceraldehyde-3-phosphate and acetate [39,40]. To our knowledge, this is the first time that different patterns of expression in TKT and TKTL1 in NSCLC progression have been shown in the same tissue samples.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary studies have also indicated that the inhibition of the PPP minimizes tumor growth [13,36,37]. Although it has been reported that TKTL1 contributes to total transketolase activity [38], with a similar metabolic role to TKT, this protein also seems to participate in other metabolic processes such as DNA hypomethylation, fatty acid synthesis, and even the one-substrate reaction catalyzing the transformation of xylulose-5-phosphate into glyceraldehyde-3-phosphate and acetate [39,40]. To our knowledge, this is the first time that different patterns of expression in TKT and TKTL1 in NSCLC progression have been shown in the same tissue samples.…”
Section: Discussionmentioning
confidence: 99%
“…This study for the first time shows that resveratrol directly inhibits mRNA and protein levels of TKTL1. TKTL1 is an enzyme known to promote nucleotide synthesis by providing the precursor molecule ribose-5-phosphate [19]. Metabolic reprogramming and increased glucose utilization, leading to Warburg effect is hallmark of cancer cells [20].…”
Section: Discussionmentioning
confidence: 99%
“…Recent work suggests that the enzyme transketolase-like 1 (TKTL1) may resemble its bacterial counterpart phosphoketolase (Heath et al, 1958) (Schramm et al, 1958) in terms of its capability of cleaving xylulose-5-phosphate into GAP and acetate (Diaz-Moralli et al, 2016). GAP is diverted back to glycolysis while acetate can be utilized to replenish acetyl-CoA for lipid synthesis.…”
Section: Acetate Metabolism and Alternative Sources Of Acetyl-coamentioning
confidence: 99%
“…With these quantitative results, the authors concluded that acetate is the dominant source of labeling for acetyl-CoA under hypoxic conditions (Kamphorst et al, 2014) (Mashimo et al, 2014). In addition, the TKTL1 activity was suggested through a 1,2- 13 C 2 -glucose labeling experiment in which the labeling pattern of lactate was altered following genetic knockdown in a manner consistent with the presence of the cleavage reaction catalyzed by TKTL1 (Diaz-Moralli et al, 2016). …”
Section: Acetate Metabolism and Alternative Sources Of Acetyl-coamentioning
confidence: 99%